ANALISIS PERAN TENAGA PROMOSI KESEHATAN DALAM EDUKASI MASYARAKAT TENTANG PEMBERIAN VAKSINASI COVID -19 DI PUSKESMAS SE-KOTA KENDARITAHUN 2022 - Lade Albar Kalza; La Ode Liaumin; La Ode Ahmad Saktiansyah; Syam Sinar Syamsuddin; Ince Ummi Kalsum Aziz; Divaya Ananda Inayah Arsan (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
To support the prevention of Covid-19 through vaccination, good health promotion is needed, of course, using simple language that is easy for the public to understand. The purpose of this study was to describe the role of health promotion workers in public education about Covid-19 vaccination at the Kendari city health center in 2022. This type of research is qualitative, namely to look at and describe the role of health promotion workers in education. The main informants in this study consisted of: Health Promotion Officers as key informants and Heads of Health Centers as regular informants. The results showed that the role of Puskesmas management, in this case the health promotion officers at the Puskesmas, was good according to the 2020 Indonesian Ministry of Health technical guidelines. The media used in health promotion helped health promotion officers at the Kendari City Health Center such as x banners, mobile ambulances, Facebook, whatsapp groups, instagram, flyer, banner. In stakeholder engagement, health promotion officers involve across sectors. Before leaving the field, health promotion officers coordinate with sub-district heads, village heads confirm with RT/RW. One of the innovations that was carried out was an activity program called "MONDOTAMBE" so that officers brought ambulances around to carry out educational counseling activities.